Web-Based Payroll Application Design and Development Using Rapid Application Development - Michael Jardine Gunawan; Rudi Sutomo (Fakultas Ilmu Komputer, Universitas Dian Nuswantoro, 2023)
Payroll is a system used by a company to manage the payment of the employees. The payroll system makes it simpler for HR to pay all employees' salaries each month. It is challenging for employees who work from home (WFH) to be present due to the COVID-19 epidemic. The HR department needs help overseeing and monitoring employee absences and regulating compensation. In response to these issues, a web-based information system was developed to simplify employee attendance tracking and to aid the Human Resource Division's (HRD) supervision and management of staff tasks and compensation. The system has undergone testing in the employee attendance phase, the validation process by the HRD Division and checking the results of the test and several factors starting from logging in to the payroll reporting process and the results of the UAT test on average meet the success rate indicators to be implemented into the company.